Life history changes of two reef fish species in exploited and unexploited marine environments in South Africa - Buxton, Colin David (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1988)
A detailed investigation into the life histories of Chrysoblephus laticeps and c. cristiceps in exploited and unexploited marine environments on the south-east coast of southern Africa is presented. The study provided information necessary for the evaluation of marine reserves as a management option for these and similar reef species. Visual underwater assessments showed a clear spatial separation between adults and juveniles of both species, suggesting a recruitment of juveniles into shallow water followed by a gradual outward migration into deeper water with age. Denslty estlmates of C. laticeps in the Noordhoek (0.0064 fish/mÂ²) and Tsitslkamma (0.0254 fish/mÂ²) areas were significantly different and were attributed to exploitation. Within area differences in density were also significantly correlated with temperature) depth and substratum relief. Similar comparisons for C. cristiceps were not possible because these fish shied away from divers. Habitat preferences were mirrored in the diets of both species which fed on a wide variety of reef associated benthic animals. Size of prey appeared to be gape limited, only larger fish being able to manipulate prey. Quantitative differences between the diets of fish sampled in different areas were a reflection of differences in available prey and not related to the relative density of predators. The dietary characteristics recorded in these fish were typical of search hunters. An age and growth study based on the examination of sectioned otoliths showed that both species were slow growing and long lived. Maximum recorded ages were 18 and 22 years for C. laticeps and C. cristiceps respectively. Growth rates in exploited and unexploited areas were not significantly different although there was an indication that growth was slower in the exploited areas for C. cristiceps. Several inconsistencies in otolith interpretation and terminology were evaluated. Contrary to other South African studies the results suggested that somatic growth was fastest just after spawning. This coincided with the winter months and was reflected by the deposition of a hyaline zone in the otolith. Two independent estimates, the Pauli derivation and visually assessed length frequency analysis, produced the same value for total mortality of C. laticeps in the Tsitsikamma area (0.2). This result, together with a significant difference in the rate of fishing mortality at different areas along the coast suggested that the populations sampled were discrete and supported the postulate that both species were sedentary. Further support was obtained from a mark-recapture study. Although sample numbers were low the results showed no evidence of large scale migratory patterns in these fish. An investigation of the reproductive biology of both fish showed that they were protogynous hermaphrodites, all males being derived from females with no evidence for polyandry. Males were shown to be capable of mating with a number of females and this, together with monandry, monochromatism and a small testis size, suggested a polygynous mating system in both species. Observations of the courtship behaviour in captive c. laticeps also supported polygyny. A significant difference in the mean size at sex reversal between unexploited and exploited populations supported the postulate that sex reversal was independent of the size or age of the animal. The size at which sex reversal occurred appeared to be dependent on sex ratio. A detailed yield per recruit analysis of the response of the population to different levels of fishing mortality and size at recruitment (t [subscript]r), showed that sex reversing species were particularly vulnerable to over fishing. This was due to a dramatic decline in the number of surviving individuals past t[subscript]r which resulted in a skewing of the sex ratio towards females. Evidence is presented to show that current legislation is inadequately protecting the spawner stock of both species. In conclusion it is shown that longevity, sex reversal, restricted movements and the occupation of a demersal habitat make these species particularly vulnerable to over exploitation in a size- selective fishery. The sustained yield in the linefishery is suggested to be a result of distant recruitment from relatively unexploited populations rather than the adequacy of current conservation measures. The need to protect the spawner stock is emphasised and the use of marine reserves as an additional protection for sedentary reef-dwelling species is therefore advocated.
Keywords: Reef fishes -- Africa, Southern; Chrysoblephus laticeps; Chrysoblephus cristiceps